2014
DOI: 10.1097/sap.0b013e3182605674
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Retrograde Limb of Internal Mammary Vein in Autologous Breast Reconstruction With DIEAP Flap

Abstract: The retrograde limb of the IMV seems to be a safe alternate recipient vein in DIEAP and muscle sparing free TRAM autologous breast reconstruction. This study does not identify a significant reduction in overall fat necrosis or overall complications when using the 2 venous repair techniques versus the simple venous repair technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 27 publications
3
23
0
3
Order By: Relevance
“…The retrograde venous drainage of the IMV inferior (or retrograde) limb could be a second recipient vessel for additional venous drainage, as previously described . However, the debate is still ongoing in the literature because of the recent discovery of the presence of valves in the IMV that could interfere with the physiological venous drainage .…”
mentioning
confidence: 85%
“…The retrograde venous drainage of the IMV inferior (or retrograde) limb could be a second recipient vessel for additional venous drainage, as previously described . However, the debate is still ongoing in the literature because of the recent discovery of the presence of valves in the IMV that could interfere with the physiological venous drainage .…”
mentioning
confidence: 85%
“…Similarly, Lee et al also reported no statistically significant difference in the incidence of total or partial flap loss and fat necrosis between the two groups. In the study by Al‐Dhamin et al the incidence of not only perfusion‐related complications but also other complications including wound infection, dehiscence and hematoma was similar between the superdrainage group and the control group.…”
Section: Resultsmentioning
confidence: 86%
“…As the experience of DIEP flap breast reconstruction has accumulated and the importance of SIEV in the venous drainage of abdominal flaps has been demonstrated, active applications of SIEV have been attempted, including prophylactic superdrainage using SIEV to reduce the incidence of flap congestion and subsequent complications. Several studies have investigated the potential efficacy of prophylactic venous superdrainage using SIEV . However, none succeeded in demonstrating significant benefits of SIEV superdrainage in reducing the incidence of perfusion‐related complications including total or partial flap loss, although those in decreasing the flap congestion rate were shown by some studies .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations